A systematic review of health sector responses to the coincidence of disasters and COVID-19 - Sanaz Sohrabizadeh; Shiva Yousefian; Amirhosein Bahramzadeh; Mohammad Hossein Vaziri (BMC, 2021)
Abstract Background In December 2019, the Chinese city of Wuhan reported a novel pneumonia caused by COVID-19. While the COVID-19 pandemic has been increasingly affecting the world, the occurrence of disasters resulted in complex emergencies. The present review is aimed to identify the literature focused on health system response to coincidence of COVID-19 and disasters as well as describing their finding, implications and lessons-learned. Methods This study was conducted and reported based on PRISMA guideline. The databases of Web of Sciences, PubMed, Scopus, Google Scholar and World Health Organization Library were searched. The inclusion criteria were all forms of published articles which investigated the coincidence of disasters and COVID-19 pandemic. Using the title and abstract screening, the selections of studies were performed by two researchers. Once, the relevant papers were finalized, the analysis was done in two parts of descriptive analysis and implications for health systems. Results Out of 1245 studies generated by initial search, a number of 13 articles was selected for final analysis. Earthquake was the most frequent disaster which its coincidence with COVID-19 was studied by researchers (31%). The implications of researchers for healthcare system were explained in three sections of climatic events, earthquakes and all hazard approach in relation to COVID-19. Conclusion Extracting the lessons learned from the regions affected by disasters at the time of COVID-19 pandemic can be helpful for healthcare professionals and policy-makers to improve their preparedness and response during disasters and a serious pandemic such as COVID-19. Further research is needed to identify the factors which strengthen the preparedness of health system for the dual risk of natural hazards and pandemics.